Intellectual Capital and Company Profile Effects on Supply Chain and Earning Per Share based on the Operational Management - Ruhiyat Taufik; Ria Kurniawati (International Journal of Supply Chain Management, 2019)
The main objective of this study is to examine the effect of intellectual capital, debt policy, company size, supply chain and liquidity on earnings per share and dividends per share as intervening variables in companies registered in the LQ 45 stock market index that consists of 45 companies for the 2014-2016 period in Indonesia. Using a purposive sampling method obtained data (panels) of 60 observation data from 20 companies. Multiple regression analysis is used to analyze two models. Model 1 analyzes the influence of intellectual capital, debt policy, company size and liquidity on dividends per share and model 2 analyzes the effect of intellectual capital, debt policy, company size and liquidity on supply chain and consequently earnings per share by including dividend per share as an interprening variable. The first Analysis regression Model 1 found that supply chain, human capital efficiency, debt policy, company size, and liquidity, statistically significant affected dividend policy, other variables did not influence. The second analysis regression of Model 2 Â based on the operational mamnagement (through variable intervening) found that only dividends per share were statistically significantly affecting earnings per share (EPS). In model 1 the adjusted R square value is very low, this means that the independent variable cannot explain changes in the dependent variable whereas in model 2 it is very high, this means that the independent variable is able to explain changes in the dependent variable.